Precarious Employment and Well-Being: Insights from the COVID-19 Pandemic. Issue 1 (February 2023) - Mai, Quan D.; Song, Lijun; Donnelly, Rachel
While precarious employment is not a new concept, it has been brought to the center of scholarly and public discourse worldwide by the unprecedented COVID-19 pandemic. This essay delineates how precarious employment shapes well-being and situates that relationship in the context of the COVID-19 pandemic. The essay also provides an overview of how the nine articles boldly investigate how these two layers of global risk—precarious employment and the pandemic—interact to shape individuals' well-being. In addition to advancing theoretical and empirical knowledge by analyzing timely data from diverse sources and populations, these articles call for more efforts on worker protection reforms and government financial support.